Dynamics of the metal-dependent transcription factor complex in vivo at the mouse metallothionein-I promoter - Daniels, Patrick J. (Oxford University Press, 2003)
The in vivo association of transcription factors with the metallothionein-I promoter was examined using chromatin immunoprecipitation (ChIP) assays. The results demonstrated that c-fos is rapidly recruited along with the metal response element-binding transcription factor-1 (MTF-1) to this promoter in response to zinc or cadmium, and that this recruitment is reversed in the visceral yolk sac by a zinc-deficient diet in vivo, and in cultured cells after lowering the zinc concentration in the medium or during prolonged zinc exposure. In contrast, the interactions of c-jun, USF-1, USF-2 and Sp1 with this promoter are metal-independent. Studies of knockout cells revealed that the recruitment of c-fos to the MT-I promoter requires MTF-1, but that c-fos is not essential for recruitment of MTF-1 and metal-induction of MT-I gene expression. Studies of Hepa cells stably-transfected with reporter genes driven by the MT-I promoter suggested two in vivo binding sites for USF-1 and -2. In contrast, Sp1 was apparently associated with a single binding site (upstream of –153 bp). In addition, maximal recruitment of c-fos by metals required sequences and/or other proteins that interact upstream of –153 bp. In summary, these studies extend our understanding of the complexity and dynamics of the transcription factor complex that forms at the MT-I promoter in vivo in response to metals.